Era of convergence in revenue management - Venkat, Ramesh (Henry Stewart Talks, 2009)
Revenue streams, Cost streams, Pricing trends, The transaction based model, The relationship based model, Optimization: a hybrid model, Future revenue management models, The current model, The enterprise model, Convergence